Linguistic and cultural features of everyday communication (on the example of English and Uzbek languages) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article examines the linguistic and cultural peculiarities of everyday communication in English and Uzbek. It highlights how cultural values, social norms, and linguistic structures shape conversational patterns, speech etiquette, and the use of idiomatic expressions. By analyzing common greetings, requests, politeness strategies, and non-verbal cues in both languages, the study identifies similarities and differences that impact intercultural communication. The research emphasizes the role of pragmatics, sociolinguistics, and cultural context in shaping language use in daily interactions. The findings contribute to a better understanding of cross-cultural communication and offer insights for language learners and the development of intercultural competence.